Relation between ultrasonic properties, rheology and baking quality for bread doughs of widely differing formulation. (24th October 2016) - Peressini, Donatella; Braunstein, Dobrila; Page, John H; Strybulevych, Anatoliy; Lagazio, Corrado; Scanlon, Martin G
Abstract: BACKGROUND: The objective was to evaluate whether an ultrasonic reflectance technique has predictive capacity for breadmaking performance of doughs made under a wide range of formulation conditions. Two flours of contrasting dough strength augmented with different levels of ingredients (inulin, oil, emulsifier or salt) were used to produce different bread doughs with a wide range of properties. Breadmaking performance was evaluated by conventional large‐strain rheological tests on the dough and by assessment of loaf quality. The ultrasound tests were performed with a broadband reflectance technique in the frequency range of 0.3–6 MHz. RESULTS: Principal component analysis showed that ultrasonic attenuation and phase velocity at frequencies between 0.3 and 3 MHz are good predictors for rheological and bread scoring characteristics. CONCLUSIONS: Ultrasonic parameters had predictive capacity for breadmaking performance for a wide range of dough formulations. Lower frequency attenuation coefficients correlated well with conventional quality indices of both the dough and the bread. © 2016 Society of Chemical Industry